Content validation of training means for taekwondo - Angelo, R.; Drummond, M.; Couto, B.; Teoldo, V.; Goncalves, R.; Pedrosa, G.; Szmuchrowski, L. (Archives of Budo, 2015)
Background and Study Aim: The validation of training means can efficiently direct the selection and prescription of training means for taekwondo beyond consolidated knowledge about this sport. The objective of the present study was the list of exercises employed during taekwondo training, categorize these exercises in training means and perform the content validation of these means. Material and Methods: Seven coaches from the Taekwondo Brazilian Selection Team participated in the first phase of this study by listing the exercises. In the second phase, five experts in sports training with expertise in taekwondo modality collaborated in the study by judging the exercises. The content validation was tested using the content validity coefficient on three indicators: clarity of language, practical relevance and theoretical relevance. The categorization of the exercises was checked by Kappa Cohen`s coefficient. The intra- and inter-judge variability was assessed using the intraclass correlation coefficient and the average Kappa Cohen`s coefficient. Results: The content validity coefficients were 0.82, 0.86, and 0.83 for clarity of language, practical pertinence and theoretical relevance, respectively. Kappa Cohen`s coefficients for the categorization of theoretical dimensions confirmed a moderate level of agreement among the judges for the three dimensions used: general, special and specific training means. The results of the intraclass correlation coefficient and the average test/re-test kappa values were considered good and substantial, respectively. Conclusion: The results of this study indicate that is possible to elaborate and validate a catalogue of training means for taekwondo. Thus, a tool was produced that can be used as a theoretical framework in the organization of planning, registration and analysis of sports training loads.